Vietnam-China relations in 1975-1978: approached from the perspective of disputes and conflicts (Revista de Investigaciones Universidad del Quindío, 2021)
Due to geographical factors as well as many different subjective and objective ones, the relations between Vietnam and China have an important position with direct influence and multi-dimensional impact on the development of Vietnam. Historical facts show that whenever Vietnam handles bilateral and multilateral relations with China well, it will create a favorable international environment and ensure security and peace for the development of the country. Since the official establishment of diplomatic relations between the two countries (1949) to 1975, mutual support and assistance have always been at the core. Logically speaking, after 1975, the traditional relations between the two countries should have been further strengthened and developed. However, after the Vietnam War (1975) and under the impact of many subjective and objective factors, increasingly serious conflicts arose in the Vietnam - China relations, leading to the termination of diplomatic relations between the two countries in 1978. Of which there are three major disputes regarding the issues of Chinese-Vietnamese people; Democratic Kampuchea; and the East Sea and terrestrial border.
Keywords: dispute; conflict; relations; Vietnam-China; 1975-1978